Effect of Chewing on the Expression of Salivary Protein Composition: A Systematic Review. Issue 3 (17th January 2020) - Al‐Manei, Khaled; Almotairy, Nabeel; Bostanci, Nagihan; Kumar, Abhishek; Grigoriadis, Anastasios
Abstract: Salivary proteins have an imperative role in the maintenance of oral health and repairing mechanisms of injured tissues. However, there is paucity of information reported in the literature about the influence of chewing activities on the secretion or expression of salivary proteins. The purpose of this systematic review is to evaluate the effect of chewing on the expression of salivary proteins composition in healthy individuals. A thorough systematic search shows 14 eligible studies for the review. The results of the systematic review show the effect of chewing on total protein concentration, alpha‐amylase (α‐amylase), peroxidase, lysozyme, immunoglobulin A (IgA), and mucin. Six papers concluded that chewing has a little or no effect on total protein concentration, α‐amylase, peroxidase, lysozyme, and IgA activities. Five papers reported a negative (decreasing) effect of chewing on the function of total protein, α‐amylase, IgA, and mucin. Only two papers showed an increase in total protein and IgA function upon chewing stimulation. The results of this systematic review indicate that more standardized evidence‐based research is required for better assessment of chewing effects on salivary proteins. Within the limitations of this review, the existing evidence suggests that chewing in healthy people has minimum effect on the expression and activities of salivary proteins.